2019
DOI: 10.1590/0104-6632.20190361s20180185
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Oleic Acid in a Semi-Batch Bubble Reactor for Biodiesel Production

Abstract: A semi-batch bubble reactor has been developed to produce fatty acid ethyl ester (biodiesel) by acid-catalyzed esterification of oleic acid with superheated ethanol vapor. In this paper, the effects of reaction temperature (110, 130 and 150°C), ethanol volumetric flow rate (1.35, 2.50 and 3.65 mL/min) and vapor bubble size on the reactor performance were evaluated. The results demonstrated that temperature and volumetric flow rate have significant effects on the chemical reaction, gas phase solubility and mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…For instance, ethanol was used instead of methanol in these reactions, which is less reactive for esterifcation. Te investigated temperature ranged between 323 and 343 K, which is a milder range compared to other papers that employed overheated alcohols (>373 K), as demonstrated in the studies by Pinnarat and Savage [22] and Silva et al [6]. Notably, in Table 3, it is observed that Cannilla et al [24] achieved a 98% conversion in ethanol esterifcation; nevertheless, the authors used a catalyst dosage more than 7 times higher than the mass employed in this study.…”
Section: Evaluation Of the Operating Variables Of The Atomizationmentioning
confidence: 65%
See 2 more Smart Citations
“…For instance, ethanol was used instead of methanol in these reactions, which is less reactive for esterifcation. Te investigated temperature ranged between 323 and 343 K, which is a milder range compared to other papers that employed overheated alcohols (>373 K), as demonstrated in the studies by Pinnarat and Savage [22] and Silva et al [6]. Notably, in Table 3, it is observed that Cannilla et al [24] achieved a 98% conversion in ethanol esterifcation; nevertheless, the authors used a catalyst dosage more than 7 times higher than the mass employed in this study.…”
Section: Evaluation Of the Operating Variables Of The Atomizationmentioning
confidence: 65%
“…Much of biodiesel currently produced is obtained through esterifcation or transesterifcation reactions between oils or fat with methanol to produce methyl esters from fatty acids [5][6][7][8][9][10][11]. Te acquisition of these raw materials (mainly triglycerides) in the biodiesel value chain represents the main production cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the batch process, the semi-batch mode is characterized by a high operation cost, low production rate, and high energy consumption. There is a high rate of human intervention during the process leading to a highly strenuous and labor-intensive process [ 60 , 61 , 62 ]. Figure 6 shows the schematic diagram of a semi-continuous flow reactor for biodiesel production as reported by Malpartida et al [ 63 ].…”
Section: Modes Of Biodiesel Production In Reactor Technologiesmentioning
confidence: 99%
“…Biodiesel possesses a relatively high flash point, thus making it have low volatility; hence, it is safe in terms of transportation and handling in comparison with petroleum diesel. Biodiesel also possesses good lubrication properties, which is an advantage to the engine since it reduces engine wear and lengthened the engine's life span [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%